A water balance simulation model for teaching and learning – WaS - Hess, Tim M.; Counsell, Chris (Cranfield University, 2008)
Developed by HR Wallingford and Cranfield University (with support from the UK Department for International Development), WaSim is a computer-based training package for the teaching and demonstration of issues involved in irrigation, drainage and salinity management. WaSim is a daily water balance model that simulates the soil water / salinity relationships in response to different management strategies (e.g. drainage designs and water management practices) and environmental scenarios (e.g. weather data, soil types, cropping patterns).
Keywords: Irrigation; Drainage; Salinity; Water Balance; Teaching; Simulation